What's in a Brand Name? Assessing the Impact of Rebranding in the Hospitality Industry. (December 2015) - Tsai, Yi-Lin; Dev, Chekitan s.; Chintagunta, Pradeep
In the context of the U.S. lodging industry (1994–2012), the authors empirically quantify the effects of the two main factors driving the rebranding effects identified by the theoretical branding literature—(1) the brand effect and (2) the interaction effect between the product (the hotel property) and the brands involved—on occupancy rate and other hotel performance indicators. They find that, on average, rebranding results in approximately a 6.31% increase in occupancy rates; 60% of this effect can be attributed to the brand identities (e.g., Holiday Inn) before and after rebranding while the remaining 40% is attributable to the interaction effect. The authors also find heterogeneity in the property–brand interaction effect of rebranding along various observable characteristics of the hotels. They assess the robustness of the results to various model assumptions and alternative instruments; in addition, they use matching estimators for analysis and exploit rebranding as a consequence of hotel mergers as a means of measuring rebranding effects. Finally, the authors consider the impact that rebranding might have on competitors' properties. Their approach to measuring rebranding effects can be applied broadly to firms and industries experiencing a decoupling of the individual components of their value chain.